(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Currently, the mortality rate from terminal stage liver fibrosis - cirrhosis - ranks 9th in the world among all causes of death and 6th among people of working age, amounting to 14 to 30 cases per 100 thousand people. The article presents current data on the methods used for the diagnosis of liver fibrosis. To date, liver biopsy, the study of direct and indirect serological markers, as well as instrumental